Pelibatan Human Intelligence Dan Techno Intelligence Dalam Menghadapi Jaringan Terorisme Di Sulawesi Tengah - Pinora, Joseph Ananta (UI Scholars Hub, 2020)
The problem raised in this study is about the role of human intelligence and techno intelligence when facing the dynamics of the movement of terrorist networks in the middle of the wilderness in Central Sulawesi Province. Meanwhile, the purpose of this study is to determine the role and implementation of information gathering in special intelligence operations. A number of theories used by researchers are intelligence theory, technology utilization theory, strategy theory and cooperation theory. Where the approach used in this research is a qualitative approach, with a descriptive type that utilizes case study models in certain areas. The researcher used the technique of observation, interview, discussion and document study. Furthermore, the data obtained were analyzed using an interactive analysis model and then validated. There are three roles described in this intelligence operation, namely the role of investigation, security and intelligence gathering, where the three activities are carried out by human intelligence and techno intelligence simultaneously. Keywords: Intelligence, Human, Technology, Strategic and Cooperation